PENGUJIAN BAKU MUTU LOGAM NIKEL PADA TEKSTUR TANAH YANG BERBEDA DENGAN INDIKATOR TANAMAN PADI - Ina Zulaehah; S Sukarjo; E S Harsanti (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Fertilizers and pesticides application in the agricultural sector provide a significant benefit in agricultural production. However, the use of fertilizers and pesticides continuously can be a harmful effect on the condition of the agricultural environment and the living things around it. Heavy metal pollution from the use of fertilizers and pesticides can cause health problems in humans, animals, and soil. Nickel is a dangerous heavy metal. The purpose of this study was to obtain the value of nickel-metal quality standards in two types of soil texture with rice as an indicator plant. This nickel quality standard testing activity was carried out in 2018 at the Indonesian Agricultural Environment Research Institute. Light textured soil was obtained from Bantul and heavy textured soil from Lamongan and Ngawi. Soil samples were tested for the adsorption of heavy metals using the Langmuir approach. A pot experiment was conducted at the screen house for heavy metals calibration in the soil. The results of the regression of the nickel content in the soil and rice can be seen as the quality standard value. Estimated quality standards in light-textured soils (Bantul) was 1.388 mg kg-1, heavy-textured soils (Lamongan and Ngawi) was 1.855 mg kg-1 and 1.697 mg kg-1, respectively. The value of nickel-metal quality standards in the clayey soils are higher than those in the light-textured soils